ACADEMIC ESSAY (EXAMPLES): METHODOLOGICAL FOUNDATION FOR THE ORIENTATION OF THE UNIVERSITY STUDENT - Doubront Guerrero, Luis Gerardo (2023)
The research to be presented has the purpose of proposing a methodological foundation of the academic essay for the orientation of the university student. In this way, the study is circumscribed in a dialogic encounter from the perspective of philosophical hermeneutics where the search for meaning, meaning and truth converge in the texts on the characteristics of an academic essay in its typology (Argumentative, Expository or Analytical), contextualizing its methodological structure and its way of communicating academic writing with well-founded positions to differentiate doxa from episteme. Methodologically, a qualitative approach is expressed taking into account the hermeneutic circle as a research method circumscribed in the interpretive paradigm. It is concluded that the structure of an academic essay has a formal character where the authors must base the purpose of the postulates that they accept and share within the abstractions and rhetoric of their statements.